Evaluation of molecular markers in osteogenic differentiation of mesenchymal stem cells - Ishiy, Felipe Augusto André (2016)
The use of stem cells is a promising therapeutic approach for tissue engineering by their ability to boost tissue regeneration, and to model in vitro human genetics disorders since it provides continuous supplies of cells with differentiation potential. Our study has been focused in the identification of molecules or mechanisms that could contribute to a better osteogenesis in mesenchymal stem cells (MSC). To achieve our goals we have explored the osteopontential differences of stem cells from different sources. In this regard, we have observed that MSCs from human exfoliated deciduous teeth (SHED) presented higher in vitro osteogenic differentiation potential (OD) as compared to MSCs derived from human adipose tissue (hASCs). Through microarray analysis and cell sorting, we have shown that IGF2 and CD105 expression levels contribute to these osteopontential cell differences, that is, higher IGF2 expression levels and lower CD105 expression levels were associated with the increased osteogenic potential of SHED as compared to hASCs. The molecular mechanisms associated with the diferent expression levels of IGF2 and CD105 in these cells were also investigated. Despite the advantages of adult MSCs they can exhibit drawbacks such as restricted self-renewal and limited cell amounts. Induced Pluripotent Stem Cells (iPSC) technology has emerged as an alternative cell source, as they provide more homogeneous cellular populations with prolonged self-renewal and higher plasticity. We verified that the OD of MSC-like iPSC differs from MSCs and it depends on the iPSCs originating cellular source. Comparative in vitro osteogenesis analysis showed higher osteogenic potential in MSC-like cells derived from iPS-SHED when compared with MSC-like cells from iPS-FIB and SHED. iPSCs can be also used as a tool to model genetic disorders. We have thus proposed to verify if it could be possible to in vitro model Treacher-Collins syndrome, a condition with deficient craniofacial bone development. We have compared the effects of pathogenic mutations in TCOF1 gene in cell proliferation, differentiation potential between MSCs, dermal fibroblasts, neural-crest like and MSC-like cells differentiated from iPSCs.TCS cells showed changes in cell properties anddysregulated expression of chondrogenesis markers during osteogenic and chondrogenic differentiation. In summary, the comparative analysis of stem cells of different sources allow us to identify markers that may facilitate osteogenesis and that it is possible to establish an in vitro model to Treacher-Collins syndrome